Variations of Learning Methods as Implementation of Teacher’s Pedagogical Knowledge - Rosa Diah Shinvani; Dwita Kurnia Amalia; Rindiana Evitaloka; Fery Anggara Putra; Ifit Novita Sari (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
The development of student potential can be realized through the role of teachers in the use of learning methods during the teaching and learning process. Learning methods are expected to run well during the teaching and learning process. Therefore, the teacher must be able to determine the right method of learning. Teachers must have the ability to manage learning. This ability is one part of a teacher's pedagogical competence. If a teacher has qualified pedagogical competencies, then the use of learning methods selected during the teaching and learning process certainly provides positive results for students in learning. This research aims to find out the learning methods that are often applied by teachers based on pedagogical competencies owned and subjects that are mastered. The research method used is a descriptive qualitative method, with data collection techniques using google form spread surveys. From the results of data processing, it can be known that the most dominant learning method used by teachers is the discussion method. The reason teachers choose the discussion method is to prioritize interaction between students. So that from the method of discussion learning, it is expected to stimulate the thinking power of students to dare to express their opinions.